Novel oncogenic mutations of CBL in human Acute myeloid leukemia that activate growth and survival pathways depend on increased metabolism - Fernandes, Margret S.; Reddy, Mamatha M.; Croteau, Nicole; Walz, Christoph; Weisbach, Henry; Podar, Klaus; Band, Hamid; Carroll, Martin; Reiter, Andreas; Larson, Richard A.; Salgia, Ravi; Griffin, James D.; et al. (The journal of biological chemistry, 2010)
Acute myeloid leukemia (AML) is characterized by multiple mutagenic events that affect proliferation, survival, as well as differentiation. Recently, gain-of-function mutations in the α helical structure within the linker sequence of the E3 ubiquitin ligase CBL have been associated with AML. We identified four novel CBL mutations, including a point mutation (Y371H) and a putative splice site mutation in AML specimens. Characterization of these two CBL mutants revealed that coexpression with the receptor tyrosine kinases FLT3 (Fms-like tyrosine kinase 3) or KIT-induced ligand independent growth or ligand hyperresponsiveness, respectively. Growth of cells expressing mutant CBL required expression and kinase activity of FLT3. In addition to the CBL-dependent phosphorylation of FLT3 and CBL itself, transformation was associated with activation of Akt and STAT5 and required functional expression of the small GTPases Rho, Rac, and Cdc42. Furthermore, the mutations led to constitutively elevated intracellular reactive oxygen species levels, which is commonly linked to increased glucose metabolism in cancer cells. Inhibition of hexokinase with 2-deoxyglucose blocked the transforming activity of CBL mutants and reduced activation of signaling mechanisms. Overall, our data demonstrate that mutations of CBL alter cellular biology at multiple levels and require not only the activation of receptor proximal signaling events but also an increase in cellular glucose metabolism. Pathways that are activated by CBL gain-of-function mutations can be efficiently targeted by small molecule drugs.
Gesehen am 21.02.2023